Earthworm Cast Formation and Development: A Shift From Plant Litter to Mineral Associated Organic Matter - Vidal, Alix; Watteau, Francoise; Remusat, Laurent; Mueller, Carsten W.; Nguyen Tu, Thanh-Thuy; Buegger, Franz; Derenne, Sylvie; Quenea, Katell (Frontiers in Environmental Science, 2019)
Earthworms play a major role in litter decomposition, in processing soil organic matter and driving soil structure formation. Earthworm casts represent hot spots for carbon turnover and formation of biogeochemical interfaces in soils. Due to the complex microscale architecture of casts, understanding the mechanisms of cast formation and development at a process relevant scale, i.e. within microaggregates and at the interface between plant residues, microorganisms and mineral particles, remains challenging. We used stable isotope enrichment to trace the fate of shoot and root litter in intact earthworm cast samples. Surface casts produced by epi-anecic earthworms (Lumbricus terrestris) were collected after 8 and 54 weeks of soil incubation in mesocosms, in the presence of 13C-labeled Ryegrass shoot or root litter deposited onto the soil surface. To study the alteration in the chemical composition from initial litter to particulate organic matter (POM) and mineral-associated organic matter (MOM) in cast samples, we used solid-state 13C Nuclear Magnetic Resonance spectroscopy (13C-CPMAS-NMR) and isotopic ratio mass spectrometry (EA-IRMS). We used spectromicroscopic approach to identify plant tissues and microorganisms involved in plant decomposition within casts. A combination of transmission electron microscopy (TEM) and nano-scale secondary ion mass spectrometry (NanoSIMS) was used to obtain the distribution of organic carbon and δ13C within intact cast sample structures. We clearly demonstrate a different fate of shoot- and root-derived organic carbon in earthworm casts, with a higher abundance of less degraded root residues recovered as particulate organic matter on the short-term (8 weeks) (73 mg.g-1 in Cast-Root vs 44 mg.g-1 in Cast-Shoot). At the early stages of litter decomposition, the chemical composition of the initial litter was the main factor controlling the composition and distribution of soil organic matter within casts. At later stages, we can demonstrate a clear reduction of structural and chemical differences in root and shoot-derived organic products. After one year, MOM clearly dominated the casts (more than 85 % of the total OC in the MOM fraction). We were able to highlight the shift from a system dominated by free plant residues to a system dominated by MOM during cast formation and development.